Modified porous alumina, and preparation method and application thereof
By introducing phenyl and amino modified groups on the surface and pores of porous alumina particles to form silicon oxygen bonds, the problems of lower conductivity and capacity of lithium-ion batteries at low temperatures are solved, and the conductivity and charge and discharge are improved Performance effect.
Patent Information
- Application Number
- CN202411607664.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
AI Technical Summary
The conductivity of lithium-ion batteries decreases under low temperature conditions, resulting in a significant reduction in capacity. The existing technology has problems such as increasing costs, reducing energy density and complex processes.
Modified porous alumina is used to introduce modified groups containing phenyl and amino groups on the surface and pores of porous alumina particles to form silicon oxygen bonds, thereby improving the compatibility and absorption rate of the electrolyte.
The conductivity and charge and discharge performance of secondary batteries under low temperature conditions are improved, the liquid retention performance of electrolyte is enhanced, and the problem of reduced capacity of lithium-ion batteries at low temperatures is solved.
Smart Images

Figure BDA0005130048460000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to modified porous alumina, a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are composed of positive electrodes, negative electrodes, diaphragms, and electrolytes. The positive and negative electrodes are immersed in the electrolyte, and lithium ions move between the positive and negative electrodes with the electrolyte as the medium to realize the charging and discharging of the battery. In order to avoid short circuits between the positive and negative electrodes through the electrolyte, a diaphragm is needed to separate the positive and negative electrodes. With the widespread application of lithium-ion batteries in new energy vehicles, electronic devices and other fields, the viscosity of the electrolyte increases and even partially solidifies under low temperature conditions, resulting in a decrease in the conductivity of lithium-ion batteries. The compatibility of the electrolyte, anode and diaphragm is poor, resulting in a significant reduction in the capacity of lithium-ion batteries at low temperatures. This shortcoming of lithium-ion batteries has been criticized, seriously affecting their use in cold areas.
[0003] In order to overcome the serious reduction in capacity of lithium-ion batteries under low temperature conditions, many existing technologies have provided corresponding solutions, among which the improvements are mainly aimed at three aspects. The first is to address the problem of slowing down the transportation speed of Li+ in the electrode and between the electrode and the electrolyte interface at low temperatures in lithium-ion batteries. This solution is generally to add an active agent to the positive or negative electrode to increase the low-temperature conductivity to improve the low-temperature application of lithium-ion batteries. Chinese patent CN111525089A discloses a method of adding two-dimensional silicon nanosheets to the positive and negative electrodes to increase the conductivity of the positive and negative electrodes at low temperatures to increase the capacity of lithium-ion batteries at low temperatures, and also uses a low-temperature conductive liquid. The second is to improve the low-temperature discharge performance caused by the increase in electrolyte viscosity or easy freezing at low temperatures. This method generally adds an electrolyte solvent with a lower melting point to increase its low-temperature conductivity. Chinese patents CN109560324A and CN10615925A both disclose a solution for a low-temperature electrolyte to improve the low-temperature capacity of lithium-ion batteries. The third is to add a heating device to the battery so that the lithium-ion battery is heated before charging and discharging during low-temperature applications. Chinese patent CN2056924U discloses a new utility patent that adds a heating structure to the battery to ensure that the battery can work at low temperatures.
[0004] There are still some problems in the existing technology for improving the electrolyte, positive and negative electrodes and battery structure. For example, changing the electrolyte will increase the activity of the electrolyte at room temperature, affecting safety, adding active substances to the positive and negative electrodes will greatly increase the cost, and changing the battery structure will reduce the battery energy density and increase the process steps and complexity. Therefore, a new idea to overcome the above problems is needed to improve the capacity of lithium-ion batteries at low temperatures. In view of this, the present invention is specially proposed. Summary of the invention
[0005] The purpose of the present invention is to provide modified porous alumina, a preparation method and application thereof, which can be applied to secondary batteries to increase the capacity of the secondary batteries at low temperatures.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a modified porous alumina, comprising porous alumina, wherein aluminum in the porous alumina is bonded to a modifying group, and the modifying group contains a phenyl group and an amino group.
[0008] In an optional embodiment, the modifying group contains a phenylamino group.
[0009] In an optional embodiment, the porous alumina achieves chemical bonding by reacting surface hydroxyl groups with an aniline coupling agent to form silicon-oxygen bonds;
[0010] Preferably, the silicon content in the modified porous alumina is 0.08% to 0.12%.
[0011] In a second aspect, the present invention provides a method for preparing the modified porous alumina according to any one of the aforementioned embodiments, comprising: reacting a modifier with the porous alumina in an aqueous environment to generate the modified porous alumina;
[0012] The modifier includes a compound containing both phenyl and amino groups; or, the modifier includes a phenyl-containing compound and an amino-containing compound to modify the porous alumina.
[0013] In an optional embodiment, the porous alumina has a particle size D50 of 0.3 μm-2 μm and an average pore size of 40 nm-70 nm;
[0014] And / or, the modifier is a modifier containing a silane group;
[0015] And / or, the modifier is N-phenyl-3-aminopropyltrimethoxysilane.
[0016] In a third aspect, the present invention provides a method for preparing the modified porous alumina according to the aforementioned embodiment, comprising: reacting a first aqueous solution containing a modifier and a hydrolyzing agent with a second aqueous solution containing porous alumina to obtain the modified porous alumina.
[0017] In an optional embodiment, the mass ratio of the modifier to the porous alumina is less than 6wt%, preferably 1wt%-2wt%;
[0018] and / or, the amount of the hydrolyzing agent is 1wt%-3wt% of the amount of the modifier;
[0019] And / or, the hydrolyzing agent is glacial acetic acid;
[0020] and / or, the reaction time is 20 min-40 min;
[0021] And / or, the pH of the first aqueous solution is 3-4;
[0022] And / or, after the reaction, the reaction liquid is subjected to solid-liquid separation, and the separated solid is dried and ground to obtain the modified porous alumina product with a D50 of 0.3 μm-1 μm.
[0023] In an optional embodiment, the concentration of the modifier in the first aqueous solution is 75wt%-85wt%;
[0024] And / or, the preparation of the first aqueous solution comprises: mixing a modifier, a hydrolyzing agent and water and stirring for 10 min to 20 min to obtain the first aqueous solution;
[0025] And / or, the ratio of porous alumina to water in the second aqueous solution is 0.8 mg / mL-1.2 mg / mL.
[0026] In a fourth aspect, the present invention provides an application of the modified porous alumina described in the aforementioned embodiment in a secondary battery, wherein the application includes application in a positive electrode material coating layer, a negative electrode material coating layer and a separator coating layer.
[0027] In a fifth aspect, the present invention provides a secondary battery separator, comprising a substrate and a coating disposed on the surface of the substrate, wherein the coating comprises the modified porous alumina described in the aforementioned embodiment.
[0028] The present invention has the following beneficial effects:
[0029] The modified porous alumina provided by the present invention inherits the porous characteristics, electrochemical stability and chemical stability of porous alumina. The porous characteristics are conducive to absorbing and storing electrolytes, and can better assume the functions of accelerating the infiltration and absorption of electrolytes and improving the liquid retention performance of electrolytes. On this basis, the surface and pores of porous alumina particles are modified by modifying groups. The benzene rings in the modifying groups can increase the compatibility of the modified porous alumina with the electrolyte, increase the absorption rate and storage capacity of the electrolyte, and the electronegativity of the amino groups in the modifying groups can reduce the resistance to electron movement, thereby improving the conductivity of the secondary battery under low temperature conditions. Under the synergistic effect of the benzene rings, amino groups, and pores, the charge and discharge performance of the secondary battery at low temperatures is improved. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] In view of the problem that under low temperature conditions, the viscosity of the electrolyte of the secondary battery increases and even partially solidifies, resulting in a decrease in the conductivity of the lithium-ion battery; at the same time, the compatibility of the electrolyte, the anode and the separator is poor, which leads to a significant reduction in the capacity of the lithium-ion battery at low temperatures, the present invention provides a modified porous alumina.
[0032] The embodiment of the present invention provides a modified porous alumina, comprising porous alumina, wherein aluminum in the porous alumina is bonded to a modifying group, and the modifying group contains a phenyl group and an amino group.
[0033] The modified porous alumina provided by the present invention inherits the porous characteristics, electrochemical stability and chemical stability of porous alumina. The porous characteristics are conducive to the absorption and storage of electrolytes, and can better bear the functions of accelerating the infiltration and absorption of electrolytes and improving the liquid retention performance of electrolytes. On this basis, the porous alumina is modified to introduce modifying groups containing phenyl groups and amino groups. Exemplarily, the modifying groups can have only one modifying group that includes both phenyl groups and amino groups; there can also be two modifying groups, one of which contains phenyl groups and the other contains amino groups. The surface and pores of the porous alumina particles are modified by modifying groups. The benzene rings in the modifying groups can increase the compatibility of the modified porous alumina with the electrolyte, increase the absorption rate and storage capacity of the electrolyte, and the electronegativity of the amino groups in the modifying groups can reduce the resistance to electron movement, thereby improving the conductivity of the secondary battery under low temperature conditions. Under the synergistic effect of the benzene rings, amino groups, and pores, the charge and discharge performance of the secondary battery at low temperatures is improved.
[0034] In an optional embodiment, the modifying group contains a phenylamino group.
[0035] The presence of phenylamino in the modified group not only simplifies the preparation process, but also makes it easier to combine the benzene ring and the amino group in the phenylamino group.
[0036] In an optional embodiment, chemical bonding is achieved by reacting surface hydroxyl groups in the porous alumina with an aniline coupling agent to form silicon-oxygen bonds.
[0037] Since porous alumina will inevitably come into contact with water, some hydroxyl groups will remain on the surface. The silanol groups generated by the hydrolysis of the hydroxyl groups and the coupling agent are used to dehydrate and condense to form silicon-oxygen bonds, thereby introducing phenylamino groups into the porous alumina.
[0038] The silicon-oxygen bond has a relatively high bond energy, which is beneficial to improving the stability of the modified porous alumina and especially the mechanical strength of the prepared material; at the same time, the silicon-oxygen bond in this application is also beneficial to improving the conductivity of lithium ions, which in turn is beneficial to further improving the transmission rate of lithium ions, thereby improving the overall performance of the battery.
[0039] In an optional embodiment, the silicon content in the modified porous alumina is 0.08 wt%-0.12 wt%.
[0040] The silicon content is closely related to the number of modified groups introduced. If the silicon content is too high and the number of modified groups introduced is too high, the pore structure of the porous alumina may be affected, which is not conducive to improving the low-temperature performance of the secondary battery. However, if the silicon content is too low and the number of modified groups introduced is too low, the effect of improving the low-temperature performance of the secondary battery will not be obvious.
[0041] The present invention also provides a method for preparing the modified porous alumina according to any one of the above embodiments, comprising: reacting a modifier with the porous alumina in an aqueous environment to generate the modified porous alumina;
[0042] The modifier includes a compound containing both phenyl and amino groups; or, the modifier includes a phenyl-containing compound and an amino-containing compound to modify the porous alumina.
[0043] The modifying groups in the modified porous alumina include phenyl and amino groups, wherein the presence of the amino group is also beneficial to reducing the hydrophobicity of the porous alumina, improving the dispersibility of the modified porous alumina in the aqueous coating slurry, inhibiting the agglomeration of the modified porous alumina during the preparation process, and is beneficial to the uniform dispersion of the modified porous alumina in the target product, thereby facilitating the relatively uniform distribution of the modifying groups on the surface of the modified porous alumina.
[0044] On the other hand, the introduction of amino groups makes the modified porous alumina have a certain hydrophilicity, and when the slurry is prepared later, it can also be better dispersed in the slurry, which is convenient for subsequent processing.
[0045] In an optional embodiment, the porous alumina particle size D50 is 0.3μm-2μm, specifically 0.3μm, 0.5μm, 1μm, 1.5μm, 2μm or any value between 0.3μm and 2μm, and the average pore size is 40nm-70nm, specifically 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm or any value between 40nm and 70nm; the particle size and pore structure of the porous alumina will affect the particle size and pore structure of the modified porous alumina, and thus affect the absorption rate and storage capacity of the modified porous alumina electrolyte; on the other hand, if the average pore size is too small, it may increase the difficulty of the modifier to enter the pores, which is not conducive to the distribution of the modifying group in the pores of the modified porous alumina; if the average pore size is too large, the specific surface area is relatively small, and the sites that can be bonded to the modifying group are reduced, which may reduce the distribution of the modifying group on the modified porous alumina.
[0046] In an optional embodiment, the modifier is a modifier containing a silane group, and the silane group and the hydroxyl group can react to form a silicon-oxygen bond.
[0047] In an optional embodiment, the modifier is N-phenyl-3-aminopropyltrimethoxysilane. Selecting a modifier containing an phenylamino group and introducing an amino group and a phenyl group at the same time is conducive to simplifying the preparation process; at the same time, the modifier itself can also undergo a condensation reaction to form a two-dimensional or three-dimensional network structure, which is conducive to improving the stability of the modified porous alumina.
[0048] The embodiment of the present invention also provides a method for preparing the modified porous alumina according to the aforementioned embodiment, comprising: reacting a first aqueous solution containing a modifier and a hydrolyzing agent with a second aqueous solution containing porous alumina to obtain the modified porous alumina.
[0049] The modifier containing silane groups is hydrolyzed to generate silanol groups, which then react with hydroxyl groups on the surface of the porous alumina, thereby introducing modified groups on the surface of the porous alumina.
[0050] In an optional embodiment, the mass ratio of the modifier to the porous alumina is less than 6wt%, preferably 1wt%-2wt%;
[0051] and / or, the amount of the hydrolyzing agent is 1wt%-3wt% of the amount of the modifier;
[0052] And / or, the hydrolyzing agent is glacial acetic acid;
[0053] and / or, the reaction time is 20 min-40 min;
[0054] And / or, the pH of the first aqueous solution is 3-4;
[0055] And / or, after the reaction, the reaction liquid is subjected to solid-liquid separation, and the separated solid is dried and ground to obtain the modified porous alumina product with a D50 of 0.3 μm-1 μm.
[0056] By limiting the amount of the modifier, the hydrolyzing agent, the reaction time and other parameters, the content of the modified group in the modified porous alumina can be adjusted within a preferred range, which is beneficial to improving the low-temperature performance of the secondary battery.
[0057] In an optional embodiment, the concentration of the modifier in the first aqueous solution is 75wt%-85wt%;
[0058] And / or, the preparation of the first aqueous solution comprises: mixing a modifier, a hydrolyzing agent and water and stirring for 10 min to 20 min to obtain the first aqueous solution;
[0059] And / or, the ratio of porous alumina to water in the second aqueous solution is 0.8 mg / mL-1.2 mg / mL.
[0060] By limiting the concentration of the modifier and porous alumina, the reaction rate can be adjusted on the one hand, and on the other hand, it is helpful to adjust the content of the modified group in the modified porous alumina within a better range, so as to improve the low-temperature performance of the secondary battery while ensuring production efficiency.
[0061] An embodiment of the present invention further provides an application of the modified porous alumina described in the aforementioned embodiment in a secondary battery, wherein the application includes application in a positive electrode material coating layer, a negative electrode material coating layer and a separator coating layer.
[0062] Applying the modified porous alumina in the embodiment of the present invention to a secondary battery is beneficial to improving the compatibility between the positive electrode material, the negative electrode material or the separator and the electrolyte, reducing the resistance to electron movement, and further beneficial to improving the conductivity of the secondary battery under low temperature conditions.
[0063] An embodiment of the present invention further provides a secondary battery separator, comprising a substrate and a coating disposed on the surface of the substrate, wherein the coating comprises the modified porous alumina described in the above embodiment.
[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0065] Example 1
[0066] This embodiment provides a method for preparing modified porous alumina, which specifically comprises the following steps:
[0067] (1) Take 1000 g of porous alumina powder with a particle size of 0.5 (D50) μm and an average pore size of 50 nm and put it into a 1000 ml beaker, add 1000 g of water, and stir at a speed of 1000 r / min.
[0068] (2) Weigh 20 g of N-phenyl-3-aminopropyltrimethoxysilane, add 4 g of deionized water, then add 0.2 g of a hydrolyzing agent, and stir for 15 min.
[0069] (3) Slowly add the modifier prepared in step (2) to the solution in step (1) and continue stirring for 30 minutes.
[0070] (4) The solution in step (3) is filtered, and after being filtered into a filter cake, it is placed in an oven and dried at 140° C. for 2 hours.
[0071] (5) The dried filter cake is taken out, ground, and then blown through a small air flow mill to a particle size of 0.3-1 μm.
[0072] Example 2
[0073] This embodiment provides a method for preparing modified porous alumina. The difference from Example 1 is that the average pore size of the porous alumina is too small, which is 9 nm. The specific amount of modifier and the steps are consistent with those in Example 1.
[0074] Example 3
[0075] This embodiment provides a method for preparing modified porous alumina. The difference from Example 1 is that the average pore size of the porous alumina is too large, which is 90 nm. The specific amount of modifier and the steps are consistent with those in Example 1.
[0076] Example 4
[0077] This embodiment provides a method for preparing modified porous alumina, which is different from that of embodiment 1 in that the modifier is different, and specifically comprises the following steps:
[0078] (1) Take 1000 g of porous alumina powder with a particle size of 0.5 (D50) μm and put it into a 1000 ml beaker, add 1000 g of water, and stir at a speed of 1000 r / min.
[0079] (2) Weigh 10 g each of phenyltrimethoxysilane and γ-aminopropyltriethoxysilane, add 4 g of deionized water, then add 0.2 g of a hydrolyzing agent, and stir for 15 min.
[0080] (3) Slowly add the modifier prepared in step (2) to the solution in step (1) and continue stirring for 30 minutes.
[0081] (4) The solution in step (3) is filtered, and after being filtered into a filter cake, it is placed in an oven and dried at 140° C. for 2 hours.
[0082] (5) The dried filter cake is taken out, ground, and then blown through a small air flow mill to a particle size of 0.3-1 μm.
[0083] Example 5
[0084] This embodiment provides a method for preparing modified porous alumina. The difference from Example 1 is that the amount of modifier used is too high. In step (2): weigh 60 g of N-phenyl-3-aminopropyltrimethoxysilane, add 12 g of deionized water, and then add 0.6 g of hydrolyzing agent (pure water adjusted to a pH of 3-4 with glacial acetic acid), and stir for 15 minutes.
[0085] Example 6
[0086] This embodiment provides a method for preparing modified porous alumina. The difference from Example 1 is that the amount of modifier used is too low. In step (2): weigh 6 g of N-phenyl-3-aminopropyltrimethoxysilane, add 1.2 g of deionized water, and then add 0.06 g of hydrolyzing agent (pure water adjusted to a pH of 3-4 with glacial acetic acid), and stir for 15 minutes.
[0087] Comparative Example 1:
[0088] This comparative example provides a method for preparing modified porous alumina, which is different from Example 1 in that the modified group does not include an amino group, and specifically comprises the following steps:
[0089] (1) Take 1000 g of porous alumina powder with a particle size of 0.5 (D50) μm and an average pore size of 50 nm and put it into a 1000 ml beaker, add 1000 g of water, and stir at a speed of 1000 r / min.
[0090] (2) Weigh 20 g of phenyltrimethoxysilane, add 4 g of deionized water, then add 0.2 g of a hydrolyzing agent, and stir for 15 min.
[0091] (3) Slowly add the modifier prepared in step (2) to the solution in step (1) and continue stirring for 30 minutes.
[0092] (4) The solution in step (3) is filtered, and after being filtered into a filter cake, it is placed in an oven and dried at 140° C. for 2 hours.
[0093] (5) The dried filter cake is taken out, ground, and then blown through a small air flow mill to a particle size of 0.3-1 μm.
[0094] Comparative Example 2:
[0095] This comparative example provides a method for preparing modified porous alumina, which is different from Example 1 in that the modified group does not include amino and phenyl groups, and specifically comprises the following steps:
[0096] (1) Take 1000g of porous alumina powder with a particle size of 0.5 (D50) μm and an average pore size of 50nm and put it into a 1000ml beaker, add 1000g of water, and stir at a speed of 1000r / min.
[0097] (2) Weigh 20 g of 3-(2,3-epoxypropoxy)propylmethyldimethoxysilane, add 4 g of deionized water, then add 0.2 g of a hydrolyzing agent, and stir for 15 min.
[0098] (3) Slowly add the modifier prepared in step (2) to the solution in step (1) and continue stirring for 30 minutes.
[0099] (4) The solution in step (3) is filtered, and after being filtered into a filter cake, it is placed in an oven and dried at 140° C. for 2 hours.
[0100] (5) The dried filter cake is taken out, ground, and then blown through a small air flow mill to a particle size of 0.3-1 μm.
[0101] Comparative Example 3:
[0102] This comparative example provides a method for preparing modified porous alumina, which is different from Example 1 in that the modified group does not include a phenyl group, and specifically comprises the following steps:
[0103] (1) Take 1000g of porous alumina powder with a particle size of 0.5 (D50) μm and an average pore size of 50nm and put it into a 1000ml beaker, add 1000g of water, and stir at a speed of 1000r / min.
[0104] (2) Weigh 20 g of γ-aminopropyltriethoxysilane, add 4 g of deionized water, then add 0.0.2 g of a hydrolyzing agent, and stir for 15 min.
[0105] (3) Slowly add the modifier prepared in step (2) to the solution in step (1) and continue stirring for 30 minutes.
[0106] (4) The solution in step (3) is filtered, and after being filtered into a filter cake, it is placed in an oven and dried at 140° C. for 2 hours.
[0107] (5) The dried filter cake is taken out, ground, and then blown through a small air flow mill to a particle size of 0.3-1 μm.
[0108] 5. Performance comparison table of different embodiments.
[0109] Unmodified porous alumina and the modified porous alumina obtained in each embodiment and comparative example are respectively formulated into coating slurries, coated on the Jie Li 9μm wet-process diaphragm and dried to obtain a coating film, wherein the coating slurry composition includes a dispersant, a binder, deionized water, and a wetting agent, the coating thickness is 3μm, and the drying temperature is 50°C.
[0110] The absorption speed and absorption rate of the electrolyte of the obtained coating film were tested, wherein the electrolyte composition was 50wt% of ethylene carbonate and 50wt% of propylene carbonate. The specific testing method was as follows: the coating film was cut into 20X50cm size, suspended above the electrolyte cell and the lower end was immersed in the electrolyte, the electrolyte infiltration height was recorded at different time points, and when it was completely saturated, i.e., the infiltration height no longer increased, it was taken out, weighed, and the electrolyte absorption rate was calculated.
[0111] The obtained coating film was used as a battery separator, a lithium iron phosphate positive electrode sheet, and a metal lithium sheet as a negative electrode to assemble a 2025-type button battery in a glove box, and the discharge capacity of the battery was tested at -20°C.
[0112]
[0113] According to the comparison of unmodified porous alumina, Example 1 and Comparative Examples 1-3, it can be seen that phenyl modification can achieve rapid adsorption of electrolyte and improve absorption rate, but its improvement effect on low-temperature charge and discharge performance is relatively low. Amino modification improves low-temperature charge and discharge performance more significantly, but its charge and discharge performance is not particularly excellent due to the lack of absorption capacity of the electrolyte. Epoxy modification has limited improvement effect on electrolyte absorption capacity and charge and discharge performance. And phenylamino modification is the most excellent in improving low-temperature charge and discharge performance, which benefits from two aspects. One is the improvement of electrolyte absorption capacity, and the other is the improvement of electronic conduction capacity brought by its amino group. The synergistic effect of the two brings excellent performance.
[0114] According to the comparison of Examples 1-3, it can be seen that the pore structure of the porous alumina as the raw material will also affect the modified porous alumina's absorption capacity for electrolyte and charge-discharge performance. When the average pore size of the porous alumina is within a reasonable range, the prepared modified porous alumina has better absorption capacity for electrolyte and charge-discharge performance.
[0115] According to the comparison between Example 1 and Example 4, it can be seen that the porous alumina modified by introducing a modifying group containing phenylamino groups has better charge and discharge performance of the electrolyte compared with the case where amino groups exist in some of the modifying groups and phenyl groups exist in some of the modifying groups.
[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified porous alumina, characterized in that: The invention comprises porous alumina, wherein aluminum in the porous alumina is bonded with a modifying group, and the modifying group contains a phenyl group and an amino group.
2. The modified porous alumina according to claim 1, characterized in that: The modified group contains a phenylamino group.
3. The modified porous alumina according to claim 1, characterized in that: The porous alumina achieves chemical bonding by reacting surface hydroxyl groups with an aniline coupling agent to form silicon-oxygen bonds; Preferably, the silicon content in the modified porous alumina is 0.08% to 0.12%.
4. A method for preparing the modified porous alumina according to any one of claims 1 to 3, characterized in that: include: A modifier is used to react with porous alumina in a water environment to generate the modified porous alumina; The modifier includes a compound containing both phenyl and amino groups; or, the modifier includes a phenyl-containing compound and an amino-containing compound to modify the porous alumina.
5. The method for preparing modified porous alumina according to claim 4, characterized in that: The porous alumina particle size D50 is 0.3 μm-2 μm, and the average pore size is 40 nm-70 nm; And / or, the modifier is a modifier containing a silane group; And / or, the modifier is N-phenyl-3-aminopropyltrimethoxysilane.
6. The method for preparing modified porous alumina according to claim 4, characterized in that: include: The first aqueous solution containing a modifier and a hydrolyzing agent is reacted with the second aqueous solution containing porous alumina to obtain the modified porous alumina.
7. The method for preparing modified porous alumina according to claim 6, characterized in that: The mass ratio of the modifier to the porous alumina is less than 6wt%, preferably 1wt%-2wt%; and / or, the amount of the hydrolyzing agent is 1wt%-3wt% of the amount of the modifier; And / or, the hydrolyzing agent is glacial acetic acid; and / or, the reaction time is 20 min-40 min; And / or, the pH of the first aqueous solution is 3-4; And / or, after the reaction, the reaction liquid is subjected to solid-liquid separation, and the separated solid is dried and ground to obtain the modified porous alumina finished product with a D50 of 0.3 μm-1 μm.
8. The method for preparing modified porous alumina according to claim 6, characterized in that: The concentration of the modifier in the first aqueous solution is 75wt%-85wt%; And / or, the preparation of the first aqueous solution comprises: mixing a modifier, a hydrolyzing agent and water and stirring for 10 min to 20 min to obtain the first aqueous solution; And / or, the ratio of porous alumina to water in the second aqueous solution is 0.8 mg / mL-1.2 mg / mL.
9. Use of the modified porous alumina according to claim 1 in a secondary battery, characterized in that: The applications include applications in positive electrode material coating layers, negative electrode material coating layers and separator coatings.
10. A secondary battery separator, characterized in that: It comprises a substrate and a coating arranged on the surface of the substrate, wherein the coating comprises the modified porous alumina according to claim 1.
Citation Information
Patent Citations
Electrolyte for ultralow-temperature-resistant lithium ion battery
CN109560324A
Low-temperature lithium ion battery considering both energy density and safety
CN111525089A
Guiding sleeve type hydraulic induction-quenching machine tool with short guiding column
CN2056924U